Lower Ordovician (Arenig) shallow-marine trace fossils of the Pochico Formation, southern Spain: palaeoenvironmental and palaeogeographic implications at the Gondwanan and peri-Gondwanan realm - Rodríguez-Tovar, Francisco Javier; Stachacz, Michal; Uchman, Alfred; Reolid, Matias (Journal of Iberian Geology, 2014)
Nineteen ichnospecies belonging to thirteen ichnogenera (Archaeonassa, Catenichnus,Cochlichnus, Cruziana, Didymaulichnus, ?Diplichnites, Gordia, Lingulichnus, Lockeia, cf.Monocraterion, Planolites, Ptychoplasma, and Rusophycus) occur in the Pochico Formation(Arenig) in the Aldeaquemada section, Sierra Morena, southern Spain, just above the ArmoricanQuartzite. They belong to the archetypal Cruziana ichnofacies, indicating a lower shoreface-upperoffshore zone. The low degree of sediment reworking may be due to a high rate of sedimentation.The trace fossil assemblage, rich in large Cruziana, is typical of the Armorican Quartzite thatdeveloped on the margins of Gondwana and peri-Gondwanan microcontinents. The distribution ofichnofauna during the Early Ordovician was partly palaeogeographically controlled, althoughichnological data from the literature point to paths of migration between Gondwana, Baltica andLaurentia. Differences between the ichnofauna of Gondwana and Baltica could be conditioned byfacies (clastics in Gondwana and carbonates in Baltica) causing a taphonomic filter, becauseCruziana requires diversified clastic deposits for preservation. The ichnofauna would also beinfluenced by trophic group amensalism between filter feeding and deposit feeding fauna, theformer prevailing in Baltica and the latter in Gondwana.